Periodic in distribution solution for a telegraph equation. (1999) - Dorogovtsev, A. Ya.
Abstract : In this paper we study an abstract stochastic equation of second order and stochastic boundary problem for the telegraph equation in a strip. We prove the existence of solutions, which are d -periodic (periodic in distribution) random processes.